Implementation of Organizational Culture as A HIMAKA (Information Science and Library Student Association) Image Forming - et. al., Haria Saputry Wahyuni.,M.I.Kom, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study discusses the implementation of organizational culture organizational culture as image formation of HIMAKA Fikom Unpad Padjadjaran University. This study aims to determine the implementation of organizational culture by HIMAKA as image shaping. This research is a qualitative study using a phenomenological approach by conducting in-depth interviews with key informants and participant observations that have been carried out to uncover the orientation of the subject or the world of their life. The research subjects are three Rovi people as the head of the association, Katon as the vice chairman, and Anggi as the head of the external department. Data collection techniques with in-depth interviews in order to obtain relevant data. The results of this study indicate that the activities carried out by the HIMAKA administrators have the aim of building the image of HIMAKA. Not only the board, but HIMAKA members were also introduced to HIMAKA's organizational culture because the image of an organization is not only in the chest of its core committee but also of all its members.